“FAKTOR-FAKTOR (UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, JENIS INDUSTRI, DAN OPINI AUDITOR) YANG MEMPENGARUHI AUDIT DELAY DI INDONESIA” (Studi Empiris Pada Perusahaan LQ-45 Yang Tetrdaftar di Bursa Efek Indonesia Periode 2011-2015) - Rika Fatmawati (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstractThis research aimed to simultaneously and partially analyze the influence of companysize, profitability, solvency, type of industry, and auditor opinion toward Audit Delay of theLQ-45 companies listed in Indonesia Stock Exchange. The method of this research wasdescriptive, classical assumptions and the population was all of LQ-45 companies listed inIndonesia Stock Exchange on the period 2011-2015. Data was collected by the method ofpurposive sampling and statistically analyzed through logistic regression analysis. The resultshowed that there was a simultaneous influence between company profitability, solvency, typeof industry and auditor opinion of the LQ-45 companies Audit Delay. In the other hand, therewas a positive signifikan partial influence between company profitability of LQ-45 companiesAudit Delay. There was negative signifikan partial influence between company solvency andthe type of industry of LQ-45 companies Audit Delay. no partial influence between size,auditor opinion of the company toward Audit Delay of the go public LQ-45 companies listedin Indonesia Stock Exchange 2011-2015.Keywords: Audit Delay factors, Financial report, LQ-45 Companies, Stock exchange